PENCEGAHAN PENJUALAN PAKAIAN BEKAS SEBAGAI UPAYA UNTUK MELINDUNGI PENYEBARAN PENYAKIT MENULAR (Analisis Yuridis Terhadap UU NO. 7 Tahun 2014 dan UU NO. 8 Tahun 1999) - Kintan Kartika Prameswari, (2023)
As time passes, the transactions of buying and selling goods and services in society have developed in various forms. There are several types of buying and selling goods and services, with the goods offered in different conditions, ranging from new to used. One example of a business model involving the recycling of used goods is the sale of imported secondhand clothing that is still suitable for use. However, the existence of the sale of imported secondhand clothing in Indonesia is actually prohibited by Indonesian laws and regulations due to the negative impact of this practice, one of which is the health of consumers because these clothes potentially carry contagious diseases. Therefore, the aim of this research is to determine how consumer protection can be achieved regarding the spread of diseases through the prohibition of the sale of imported secondhand clothing, and what responsibilities should be undertaken by sellers of imported secondhand clothing. In this study, the author employs a normative or juridical-normative research method, and the research approach used is the legislative approach. Various relevant theories and previous studies are also utilized. The research also utilizes primary and secondary data sources, and the author employs a literature review as the method of data collection. This research employs qualitative data analysis technique, which involves examining the material in a structured and comprehensive manner. Therefore, from this research, the author concludes that the Trade Law and Consumer Protection Law aim to provide a strong legal foundation for the government to protect consumer rights. Currently, there is no specific law in Indonesia that specifically regulates the prohibition of selling secondhand clothing. However, the Consumer Protection Law and Trade Law in Indonesia regulate consumer rights and protection, including in the context of purchasing secondhand clothing. Furthermore, the Trade Law and Consumer Protection Law also govern the responsibilities of business operators in the sale of imported secondhand clothing. By fulfilling these responsibilities, business operators can contribute to creating fair, safe, and sustainable trade practices.